Fungal Indole Alkaloid Biogenesis Through Evolution of a Bifunctional Reductase/Diels-Alderase - Dan, Qingyun (Nat Chem, 2019)
Prenylated indole alkaloids, such as the calmodulin inhibitory malbrancheamides and anthelmintic paraherquamides possess great structural diversity and pharmaceutical utility. Here we report complete elucidation of the malbrancheamide biosynthetic pathway accomplished through complementary approaches. These include a biomimetic total synthesis to access the natural alkaloid and biosynthetic intermediates in racemic form, and in vitro enzymatic reconstitution that provides access to the natural antipode (+)-malbrancheamide. Reductive cleavage of a l-Pro-l-Trp dipeptide from the MalG nonribosomal peptide synthetase (NRPS) followed by reverse prenylation and a cascade of post-NRPS reactions culminates in an intramolecular [4+2] hetero-Diels-Alder (IMDA) cyclization to furnish the bicyclo[2.2.2]diazaoctane scaffold. Enzymatic assembly of optically pure (+)-premalbrancheamide involves an unexpected zwitterionic intermediate where MalC catalyzes enantioselective cycloaddition as a bifunctional NADPH-dependent reductase/Diels-Alderase. Crystal structures of substrate and product complexes together with site-directed mutagenesis and molecular dynamics simulations demonstrate how MalC and PhqE, its homolog from the paraherquamide pathway, catalyze diastereo- and enantioselective cyclization in the construction of this important class of secondary metabolites.